下顎骨に発生した腺癌NOS (囊胞腺癌) の1例 - 矢郷, 香; 川本, 義明; 橋口, 隼人; 朝波, 惣一郎; 佐藤, 豊彦 (日本口腔外科学会雑誌, 2021)
We report an extremely rare case of adenocarcinoma, NOS (cystadenocarcinoma); a low-grade malignant salivary gland tumor arising in the mandible. A 64-year-old man visited our hospital because of a painless swelling in the right mandibular gingiva. The lesion appeared radiographically as a well-demarcated multilocular radiolucent area, similar to an odontogenic cystic lesion, in the right side of the mandible. There was no cervical lymphadenopathy. A segmental mandibulectomy was performed under general anesthesia, and the final histopathological diagnosis was adenocarcinoma, NOS (cystadenocarcinoma). There was no evidence of recurrence or metastasis 51 months after the operation. However, 66 months after surgery, the patient passed away due to double cancer of the lung.